The Effectiveness of Personal Carbon Trading for Sustainable Urban Development in Developing Nations: An Overview - Amita Shan; Vivek Agnihotri (International Journal of Environmental Planning and Development Architecture, 2025)
In recent decades, humankind has evolved much more rapidly than the ages. This evolution resulted in tremendous technological advancement and massive planetary degeneration. Enormous greenhouse gas emissions have resulted from the quick increase in energy and fossil fuel consumption patterns brought on by technological breakthroughs. Eventually, the scenario contributed to rising per capita carbon emissions manifolds, especially in highly populated cities. Reduced per capita carbon footprints are the goal of a number of initiatives being implemented to address this problem, including taxation, incentives, policy recommendations, etc. Personal Carbon Trading (PCT) is an innovative approach to fostering sustainable urban development by assigning individual carbon allowances and enabling citizens to trade emissions credits. The notion encourages urban dwellers to lessen their carbon footprints while raising awareness of climate change by fusing financial incentives with environmental responsibility. Cities can promote a culture of accountability and teamwork by putting PCT mechanisms in place, enabling people to take an active role in sustainability initiatives. This study examines the potential of personal carbon trading to enhance urban sustainability, analysing its implications for local economies, social equity, and behavioural change. The efficiency of PCT in lowering greenhouse gas emissions and encouraging low-carbon alternatives is demonstrated by case studies from early adopters. A thorough summary of PCT's contribution to the accomplishment of urban sustainability objectives is given, together with a discussion of obstacles like legal frameworks, public acceptance, and technology requirements. Finally, this study examines PCT and its useful approach to aligning individual conduct with broader climate objectives, improving the sustainability and resilience of the urban environment.
Keywords: Developing nations; GHG; Personal carbon trading (PCT); carbon credit; carbon footprints; sustainable development